STRENGTHENING TOTAL PEOPLE'S DEFENSE AND SECURITY SYSTEM IN THE INDUSTRIAL REVOLUTION ERA 4.0 TO FACE THE THREAT OF SIXTH GENERATION WAR - Ryamizard Ryacudu; I Nengah Putra; Susilo Adi Purwantoro (The Republic of Indonesia Defense University, 2021)
Revolution couldn’t be separated in the history of the struggle of the Indonesian nation. Experience and real evidence that the involvement of every component in the elements of the nation plays a crucial role in making Indonesia be one of the great countries in the world. This experience was adopted into a state defense system known as the Total People’s Defense and Security System. Growing globalization could be a threat to a country's sovereignty, mainly in the era of the sixth genealogy war. The purpose of this study is to develop knowledge about the importance of strengthening Sishankamrata (Total People’s Defense and Security System) in presence of industry 4.0. The method used in this study is descriptive qualitative analysis through literature studies with the development of thinking through literature studies and research tour of duty. In this study, the PMESII and VUCA construction is used. The result of this study is confirmed that strengthening Sishankamrata was needed to improve the readiness of the national defense strategy in facing the threat of the sixth-generation war. This strengthening includes strengthening the posture and capabilities of the main components, reserve components, and supporting components, and strengthen state defense as a foundation in Sishankamrata by optimizing national insight integrated with every policymaker.